Language learning through social media: a bibliometric analysis - Ahmad Sidiki, Ahmad Firdaos Syauqi; Mohamed Hamdan, Hanani; Hussain, Syedda Fareeha; Mat Pardi, Khalid; Nordin, Noli Maishara (GADING Journal for the Social Sciences, 2024)
Social media's rapid expansion greatly impacted language learning, and researchers are intrigued to discover what educational opportunities it can bring. Past studies highlight how social media improves language proficiency, motivation, and intercultural competency, highlighting drawbacks such as misinformation and distraction. To better comprehend language learning through social media, this study conducted a bibliometric analysis of research articles from 2009 to 2024, looking at research trends, significant contributors, and thematic focus areas. According to the data, there has been a consistently gradual rise in scholarly interest in social media as a language learning medium, especially during the COVID-19 pandemic. Key findings include a list of the most frequently mentioned authors, a summary of popular research topics, and an analysis of international cooperation networks. This collaborative research environment portrays the vital role that multiple authors have played in deepening the understanding of how social media is leveraged for language learning.